High-Density Lipoprotein (HDL) Triglyceride and Oxidized HDL: New Lipid Biomarkers of Lipoprotein-Related Atherosclerotic Cardiovascular Disease - Fumiaki Ito; Tomoyuki Ito (MDPI AG, 2020)
Lipid markers are well-established predictors of vascular disease. The most frequently measured lipid markers are total cholesterol, high-density lipoprotein (HDL)-cholesterol (HDL-C), LDL cholesterol (LDL-C), and triglyceride. HDL reduces atherosclerosis by multiple mechanisms, leading to a reduced risk of cardiovascular disease, and HDL-C, as a metric of HDL quantity, is inversely associated with cardiovascular disease, independent of LDL-C. However, the quality of the HDL appears to be more important than its quantity, because HDL loses its antiatherogenic functions due to changes in its composition and becomes "dysfunctional HDL". Although there is evidence of the existence of "dysfunctional HDL", biomarkers for monitoring dysfunctional HDL in clinical practice have not yet been established. In this review, we propose a new lipid panel for the assessment of dysfunctional HDL and lipoprotein-related atherosclerotic cardiovascular disease. The lipid panel includes the measurement of lipid peroxide and triglyceride contents within HDL particles.